2021
DOI: 10.54112/bcsrj.v2021i1.54
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-Mediated Transformation of Cotton (Gossypium Hirsutum L.) Using Dmo Gene for Enhanced Tolerance Against Dicamba Pesticide

Abstract: The agrobacterium based transformation of herbicide-resistant crops has modernized weed management in crops by producing cost-effective and ecosystem friendly transgenic plants. Cotton is one of the major crops which are grown worldwide due to its great economic value in textile industries.  Dicamba is a commonly used herbicide in broadleaf plants to kill a wide range of weeds in many dicotyledonous crop fields since the 20th century. In this study, Eagle 2 cotton variety was transformed with the DMO gene whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Cotton (Gossypium hirsutum L.) is one of the most important economic fiber crops, which is essential in agriculture and trade and which is grown to obtain fiber, which is used in the textile industry, and for obtaining oil from its seeds: 1 . Cotton has a tremendous economic place in the world in general and Iraq in particular, as it is considered one of the cash crops that generate profits for farmers and its uses in many industries, 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Cotton (Gossypium hirsutum L.) is one of the most important economic fiber crops, which is essential in agriculture and trade and which is grown to obtain fiber, which is used in the textile industry, and for obtaining oil from its seeds: 1 . Cotton has a tremendous economic place in the world in general and Iraq in particular, as it is considered one of the cash crops that generate profits for farmers and its uses in many industries, 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Cotton (Gossypium spp. ), is genetically diverse plant, it has four domesticated species such as G. arboreum L, G. herbaceum L, G. barbadense L. and G. hirsutum L. G. arboreum has many remarkable benefits over G. hirsutum, and has significant resistance against biotic and abiotic stresses especially drought and salinity, which makes it valuable gene pool for improving modern cotton cultivars [7][8][9] .Gossypium Universal stress Protein-2 (GUSP-2) has been identified and cloned from water stressed leaves of G. arboreum 10,11 . Sequence analysis showed that GUSP-2 is highly similar to bacterial MJ0577-type of…”
mentioning
confidence: 99%
“…Cotton (Gossypium spp. ), is genetically diverse plant, it has four domesticated species such as G. arboreum L, G. herbaceum L, G. barbadense L. and G. hirsutum L. G. arboreum has many remarkable benefits over G. hirsutum, and has significant resistance against biotic and abiotic stresses especially drought and salinity, which makes it valuable gene pool for improving modern cotton cultivars [7][8][9] .…”
mentioning
confidence: 99%